Sosialisasi Cegah Pernikahan Usia Dini Untuk Generasi Bebas Stunting Di SMA Negeri 4 Pandeglang - Lambang Satria Himmawan; Heny Sasmita; E. Egriana Handayani; Erma Noor Wahyuningsih; Siti Nur Ramdaniati; Ucu Wandi Somantri (FUNDAMENTUM : Jurnal Pengabdian Multidisiplin, 2024)
Stunting is a chronic nutritional problem caused by multiple factors, one of which is early marriage. Early marriage is still common, especially in rural areas, households with a low economy and low education. The aim of this service is through the promotion of early marriage to provide education about the dangers of early marriage as an effort to prevent stunting. By using a pre-test and post-test questionnaire, the researchers were able to determine the average number of respondents who understood the information before and after being socialized on the topics of early marriage through 3M, stunting, and reproductive health. After calculating the average, the researchers found that students at SMA Negeri 4 Pandeglang, before being given counseling had an average score of 54% and after being given counseling had an average score of 92%.